How Sustainable are Biofuels in a Natural Resource-Dependent Economy? - Nakamya, Miria (Energy for Sustainable Development, 2022)
For biofuels to promote growth in low-income agriculture-dependent economies, sustainability should be at the forefront of their biofuel programs. The high dependence on natural resources exposes such economies to resource misuse and environmental mismanagement risks. This research uses the case study of Uganda to assess the land, energy, water, and carbon footprints of maize, cassava, and sugarcane ethanol. All three pathways have positive energy balances, and the carbon footprints range between 0.89–3.12, 0.85–2.19, and 0.24–0.49 kg CO2eq/L of maize, cassava, and sugarcane ethanol, respectively. It would take about 15 years for maize ethanol, 14 for cassava ethanol, and 6 for sugarcane ethanol to break even with reference to gasoline if feedstocks were produced on converted grassland. Sugarcane ethanol is superior to maize and cassava ethanol, and its benefits derive from the carbon-neutral co-product electricity and a relatively higher ethanol yield per hectare. The study findings flag the ethanol processing stage and feedstock farming as key emission hotspots. They also reflect the emissions-reducing potential of ethanol exhibited by a decline in national emissions. Land requirements are minimal, and this demand diminishes with the improvement in crop yields. Overall, there are high prospects of economic and environmental gains. However, agricultural investment and immediate attention to poor crop yields are required alongside a regulated framework and the promotion of low-carbon energy sources.
Keywords: Ethanol; Sustainability; Environment; Emissions; CGE